Educational and Permanent Formation: Offers of Innovation in the Education of the Sciences, towards the creation of Educatives Communities. (Educational Perspectives Magazine (REPED), 2022)
The educative formation the teachers in Sciences, is for decades a fundamental factor for the changes that they propose in education. Many have been the efforts for promoting in the teachers the update of contents as also the incorporaron of methodological offers that support and favor the leaming in the students.In this context of favoring the professional constant development, it is that an alliance has taken place between the Faculty of Chemistry and Biology of the University of Santiago of Chile, PRIDE Chile and Arquimed’s Educational Services, to carry out a Diplomat in “ Innovation in education of the Sciences “, that seek to support the development of scientific and technological skills in teachers who realize scientific Education in schools and college, in addition a module of management joins, in order that the teachers possess the necessary tools to develop projeets thatallow them to increase his resources for the leaming of his students, incorporating systems the collection of date and information.The Diplomat this one raised as the first part of a process, which implies other processes as, is the use of a platform Web ( www.nativoinec.cl) for the exchange of experiences between university teachers, teachers of classroom, students, and tutors. A later stage contemplates the formation of centers of leaming for the teachers and students. These centers will be specially like a constant support to the masters, who will be able to come and to accede to different courses both in science and in science technology resources delivering him a support to her schemes of work.In the first stage, the development of the Diplomat, it has been designed by two essential concepts: 1. To achieve an interrelationship between university and educational teachers of classroom, both in the classes, laboratories and in the platform Web. 2. Use of technology for the education of the Sciences, it joins in the laboratories of the university and in addition to every educational assistant to the gradúate theie will do delivety of a kit of sensor; (pH, voltage. and temperaturel more one software of coliection of Information, for Computer, as also the use of theplatform web.The set of activities and development of tools shape the educative community called INEC (Innovation for Sciencie's Education).
Keywords: Educational and Permanent Formation, Scientific Education, Educational Community, StrategicAlliances, Diplomat in Sciencie's Education.